2010
DOI: 10.1038/hr.2009.220
|View full text |Cite
|
Sign up to set email alerts
|

Effect of body weight loss and normalization on blood pressure in overweight non-obese patients with stage 1 hypertension

Abstract: We evaluated the effects of body weight (BW) loss on blood pressure (BP) in overweight non-obese patients with stage 1 hypertension. We enrolled 376 overweight (body mass index (BMI) X25 and o30 kg m À2 ) stage 1 hypertensive patients in this prospective 12-month trial. Each patient received tailored, low caloric dietary advice. After 6 months, patients with a BW reduction o5% were excluded. Body weight, BMI, BP, fasting plasma glucose (FPG), fasting plasma insulin (FPI), leptin (pL), renin and aldosterone lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 72 publications
1
21
2
Order By: Relevance
“…Second, the fruits and vegetables group had increased urine K + excretion, consistent with increased dietary K + that is associated with BP reduction in individuals with hypertension (34). Third, the fruits and vegetables group lost more body weight than did the HCO 3 group, probably contributing to BP reduction (35).…”
Section: Discussionmentioning
confidence: 83%
“…Second, the fruits and vegetables group had increased urine K + excretion, consistent with increased dietary K + that is associated with BP reduction in individuals with hypertension (34). Third, the fruits and vegetables group lost more body weight than did the HCO 3 group, probably contributing to BP reduction (35).…”
Section: Discussionmentioning
confidence: 83%
“…Previous small or moderate sized studies have reported decreases in serum aldosterone or aldosterone excretion with modest weight loss in obese postmenopausal women 8 , young overweight/obese adults 5, 7 , middle-aged overweight/obese adults 9, 26 , and obese adults who submitted to very low calorie diets 5, 10 . Some studies have reported significant associations between reductions in circulating RAAS components and reductions in central adiposity 5, 8 or insulin resistance 5 during weight loss, though not all studies agree 7 .…”
Section: Discussionmentioning
confidence: 96%
“…18,19 In addition, reduced body weight (Table 3) with F þ V might also have contributed. 20 Furthermore, the greater Ualb decrease in CKD 2 than in CKD 1 group given F þ V was associated with greater Sys BP reduction in CKD 2 than in CKD 1 group given F þ V. Consequently, greater Sys BP reduction might have mediated the greater Ualb decrease in CKD 2 than in CKD 1 group given F þ V. Dietary Na þ reduction decreases Sys BP more in those patients with reduced than normal GFR, 21 and possibly explains greater Sys BP reduction in CKD 2 than in CKD 1.…”
Section: Discussionmentioning
confidence: 97%